Significant reduction of cell invasiveness in nanoneedle insertion into a living cell with an electron-beam-deposited probe: impacts of probe geometry, speed and vibration - Alam, Mohammad Shahidul; Penedo, Marcos; Ichikawa, Takehiko; Hosain, Mohammad Mubarak; Matsumoto, Kyosuke; Miyazawa, Keisuke; Fukuma, Takeshi (Nanoscale, 2025)
Intracellular probing of living cells using atomic force microscopy (AFM) has advanced significantly, but it requires specially designed nanoprobes to achieve precision and minimize damage. The development of focused ion beam (FIB)-milled nanoprobes enabled this progress, allowing researchers to fabricate long, sharp probes that penetrate cell membranes with reduced force. Although these FIB-milled probes have been crucial in accessing the intracellular environment, they still cause considerable membrane deformation, limiting their effectiveness in detailed measurements. In response, we developed electron beam deposited (EBD) carbon nanoprobes with varying diameters to further reduce penetration force and resulting cell disturbance. Our study reveals that, for probes of the same diameter, EBD carbon nanoprobes inflict significantly less membrane deformation than FIB-milled ones, due to their sharper tip apex. Additionally, reducing the diameter of the EBD nanoprobes further decreased the penetration force and minimized cell disturbance. We also observed that, at similar speeds, EBD nanoprobes consistently caused less damage, emphasizing the importance of both tip geometry and penetration speed in reducing the impact on cells. Oscillating the cantilever during penetration further reduced friction with the membrane, significantly reducing damage. These findings advance the precision and gentleness of intracellular AFM measurements, offering improved methods for studying cellular mechanics while preserving cell viability. This study highlights the importance of probe geometry, speed and vibration in minimizing cellular disturbance during the insertion of an electron-beam-deposited nanoprobe into living cells.